A Symptomatic Spinal Extradural Arachnoid Cyst with Lumbar Disc Herniation - Yoshinori Kadono; Takamichi Yuguchi; Yu-ichiro Ohnishi; Koichi Iwatsuki; Toshiki Yoshimine (Case Reports in Orthopedics)
Spinal epidural arachnoid cyst (EAC) is a rare, usually asymptomatic condition of unknown origin, which typically involves the lower thoracic spine. We report a case of posttraumatic symptomatic EAC with lumbar disc herniation. A 22-year-old man experienced back pain and sciatica after a traffic accident. Neurological examination revealed a right L5 radiculopathy. Magnetic resonance imaging demonstrated a cystic lesion at the L3 to L5 level and an L4-5 disc herniation; computed tomography myelography showed that the right L5 root was sandwiched between the cyst and the herniation. A dural defect was identified during surgery. The cyst was excised completely and the defect was repaired. A herniation was excised beside the dural sac. Histology showed that the cyst wall consisted of collagen and meningothelial cells. Postoperatively the symptoms resolved. Lumbar spinal EACs are rare; such cysts may arise from a congenital dural crack and grow gradually. The 6 cases of symptomatic lumbar EAC reported in the literature were not associated with disc herniation or trauma. In this case, the comorbid disc herniation was involved in symptom progression. Although many EACs are asymptomatic, comorbid spinal disorders such as disc herniation or trauma can result in symptom progression.